2022
DOI: 10.1101/2022.02.15.480542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cold-inducible promoter-driven knockdown of Brachypodium antifreeze proteins confers freeze sensitivity

Abstract: The model forage crop, Brachypodium distachyon, has a family of ice recrystallization inhibition (BdIRI) genes, which encode antifreeze proteins that function by adsorbing to ice crystals and inhibiting their growth. The genes were previously targeted for knockdown using a constitutive CaMV 35S promoter and the resulting transgenic Brachypodium showed reduced antifreeze activity and a greater susceptibility to freezing. However, the transgenic plants also showed developmental defects with shortened stem length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 94 publications
(131 reference statements)
0
7
0
Order By: Relevance
“…No changes in ice nucleation temperature were seen with non-acclimated (NA) lysates, which have no measurable AFP activity. Likewise, nucleation temperatures of lysates from miRNA BdIRI knockdown lines (prOmiRBdIRI-1e or -3c 16 ) with little to no AFP activity were not depressed, irrespective of their CA or NA treatment history, demonstrating that the attenuation of INP activity was dependent on AFP activity, as also shown by IRI assays (Figure 1). Attenuation of INP activity suggests a physical interaction between the two proteins.…”
Section: Afp-mediated Attenuation Of Inp-induced Freezing and Inp Modelsmentioning
confidence: 68%
See 1 more Smart Citation
“…No changes in ice nucleation temperature were seen with non-acclimated (NA) lysates, which have no measurable AFP activity. Likewise, nucleation temperatures of lysates from miRNA BdIRI knockdown lines (prOmiRBdIRI-1e or -3c 16 ) with little to no AFP activity were not depressed, irrespective of their CA or NA treatment history, demonstrating that the attenuation of INP activity was dependent on AFP activity, as also shown by IRI assays (Figure 1). Attenuation of INP activity suggests a physical interaction between the two proteins.…”
Section: Afp-mediated Attenuation Of Inp-induced Freezing and Inp Modelsmentioning
confidence: 68%
“…Brachypodium seeds of an inbred line, ecotype Bd21 (RIKEN, Japan) and two transgenic AFP temporal knockdown lines 16 were sown in potting soil and maintained at 4 °C in darkness for four days to synchronise germination. Seeds were moved to a climate-controlled growth chamber (Conviron GEN2000, Controlled Environments Ltd., Winnipeg, MB) at standard Brachypodium growth conditions of 70% relative humidity and 20 h days at ~150 μmol m −2 s −1 at 24 °C followed by 4 h periods with no light at 18 °C.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…No changes in ice nucleation temperature were seen with non-acclimated (NA) lysates, which have no measurable AFP activity. Likewise, the nucleation temperatures of lysates from miRNA BdIRI knockdown lines (prOmiRBdIRI-1e or -3c [ 8 ]) with little to no AFP activity were not depressed, irrespective of their CA or NA treatment history, demonstrating that the attenuation of INP activity was dependent on AFP activity, as also shown by IRI assays ( Figure 1 d).…”
Section: Resultsmentioning
confidence: 84%
“…Knockdown of the BdIRI translation products in transgenic Brachypodium as well as the heterologous expression of grass AFP in Arabidopsis have demonstrated that AFP activity confers protection against membrane electrolyte leakage subsequent to sub-zero temperature exposure [ 6 , 7 ]. Unlike AFPs from freeze-susceptible organisms, Bd AFPs do not lower the freezing point of solutions by more than ~0.1 °C, but they are very effective at IRI, or the prevention of ice crystal coalescence at high sub-zero temperatures or under freeze–thaw conditions, a property crucially important for freeze-tolerant grasses [ 6 , 8 ]. Bd AFP has been modelled based on its 67% identity to the AFP of the grass Lolium perenne ( Lp AFP), and it is predicted to have a beta-solenoid structure with two flat ice-binding motifs [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation